1991
DOI: 10.1002/jso.2930480407
|View full text |Cite
|
Sign up to set email alerts
|

Imaging‐guided and nonimaging‐guided fine needle aspiration of liver lesions: Experience with 406 patients

Abstract: The aim of the present study was to determine the diagnostic accuracy of different modes of fine needle aspiration (FNA) of liver lesions. A total of 492 FNAs were performed on 406 patients in order to confirm or to rule out focal or multifocal neoplastic disease: 29% under ultrasound (US) guidance, 3% with computed tomographic (CT) guidance, 67% preoperatively, and 1% intraoperatively without imaging guidance. Based on histologic, cytologic, and clinical findings, final diagnoses were reached in 387 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A tremendous variety of malignant neoplasms can occur in the liver, with metastases being much more common than primary neoplasms [1][2][3][4]. Tumors from almost the entire human body can metastasize to the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A tremendous variety of malignant neoplasms can occur in the liver, with metastases being much more common than primary neoplasms [1][2][3][4]. Tumors from almost the entire human body can metastasize to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…FNB of liver masses can be performed percutaneously or endoscopically under ultrasound or computed tomography (CT) guidance. The sensitivity and specificity of FNB for detection of liver malignancy are up to 94% and close to100%, respectively [1][2][3][4][5]. False positives are rare, and false negative diagnoses are most often the result of sampling error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors claim that needle size, number of passes, tumor size, and differ- entiation increase the risk of tumor seeding, 13 others state that true risk factors are unknown. 7 In terms of sensitivity, specificity, and positive predictive value, FNA 19,[34][35][36][37][38][39][40] has been shown to be comparable to NCB 36,38,40,41 in the diagnosis of malignant hepatic lesions. FNA is also associated with less patient morbidity, provides faster turn-around time, and is less costly.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that the diagnostic value of these methods is comparable 11 . With fna, sensitivity is 67%-100%, and specificity is 98%-100% [12][13][14][15] . The sensitivity of fna depends mostly on the technique and skill of the radiologist and the cytopathologist 16 .…”
Section: Diagnosismentioning
confidence: 99%